Responding to the syphilis outbreak in Japan: piloting a questionnaire to evaluate potential risk factors for incident syphilis infection among men who have sex with men in Tokyo, Japan, 2015 - Ishikane, Masahiro; Arima, Yuzo; Itoda, Ichiro; Takahashi, Takuri; Yamagishi, Takuya; Matsui, Tamano; Sunagawa, Tomimasa; Oishi, Kazunori; Ohnishi, Makoto (Western Pacific Surveillance and Response, 2016)
To respond to the syphilis outbreak in men who have sex with men in Tokyo, we created a questionnaire to determine risk factors for syphilis acquisition. The questionnaire was piloted and we report those findings, and emphasize the importance of pretesting tools that ask sensitive questions among hard-to-reach populations.